Mobile Radio Link Adaptation by Radio Channel State Prediction - Ziacik, P.; Wieser, V. (Elektronika ir Elektrotechnika, 2011)
The paper explains the prediction range adaptation and optimal setting of the sampling period of the radio signal envelope to guarantee optimal quality and capacity of the radio channel. The developed algorithms FSPRA and VSPRA provide optimal setting of the prediction range with respect to the mobile station motion. Both algorithms are compared with the algorithm without adaptation. Efficiency of algorithms and their contribution to minimization of the radio channel state prediction error, optimal prediction gain for a sufficiently large prediction range with respect to execution speed of the adaptation algorithm are evaluated. The paper focuses on using the Kalman filter to predict the radio signal fading envelope and potential implementation in the transmitter power control loop. Ill. 4, bibl. 10 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.689